Development of Environmental Education Teaching Materials Based on Class VII Middle School Entrepreneurship - Megawati, Megawati (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This research aims to develop entrepreneurship-based teaching materials in environmental education for class VII junior high school students. The development approach follows the ASSURE model, which includes potential and competency analysis, setting learning objectives, selecting methods, media and materials, student participation, as well as evaluation and improvement. After development, the teaching materials were tested on class VII junior high school students in Jambi City. Validation results by design and materials experts show product conformity with the writing procedures and curriculum used. Student responses to teaching materials show enthusiasm and improvement in environmental learning. Formative and summative evaluations are also carried out to measure the effectiveness and attractiveness of teaching materials. Comments and suggestions from experts and peers are used to make revisions to the product. The novelty of this research lies in the development of entrepreneurship-based teaching materials in environmental education for junior high school students, which can increase interest and effectiveness of learning. The implication is that the adoption of this teaching material can improve the quality of environmental learning in schools.